2013
DOI: 10.1128/iai.01453-12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of BcaA, a Putative Classical Autotransporter Protein in Burkholderia pseudomallei

Abstract: bBurkholderia pseudomallei is a tier 1 select agent, and the causative agent of melioidosis, a disease with effects ranging from chronic abscesses to fulminant pneumonia and septic shock, which can be rapidly fatal. Autotransporters (ATs) are outer membrane proteins belonging to the type V secretion system family, and many have been shown to play crucial roles in pathogenesis. The open reading frame Bp1026b_II1054 (bcaA) in B. pseudomallei strain 1026b is predicted to encode a classical autotransporter protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…In the case of BcaA, plasmid complementation showed that it is required for efficient plaque formation. In vivo studies indicated that BcaA is also required for efficient dissemination and survival of bacteria in spleen (118). In a less targeted approach, transposon mutagenesis with TnphoA was used to identify potential genes encoding surface-exposed virulence factors in enterotoxigenic E. coli.…”
Section: Gene Inactivation and Plasmid Complementationmentioning
confidence: 99%
“…In the case of BcaA, plasmid complementation showed that it is required for efficient plaque formation. In vivo studies indicated that BcaA is also required for efficient dissemination and survival of bacteria in spleen (118). In a less targeted approach, transposon mutagenesis with TnphoA was used to identify potential genes encoding surface-exposed virulence factors in enterotoxigenic E. coli.…”
Section: Gene Inactivation and Plasmid Complementationmentioning
confidence: 99%
“…Another study by Campos et al demonstrated that B. pseudomallei strain 340 bcaA and bcaB mutants displayed impaired invasion and decreased plaque formation in lung epithelial cells [13]. Furthermore, a BALB/c i.n.…”
Section: Pathogenesismentioning
confidence: 99%
“…Previous studies have examined the biological roles of all 8 ATs in B. pseudomallei (88)(89)(90). However, only the oligomeric ATs BimA (intracellular motility protein) (91), BoaA (92) and BpaC (93) (host cell adhesion proteins), and BpaB (biofilm and virulence factor) (77) have been functionally characterized in B. mallei.…”
mentioning
confidence: 99%